A Review of Valorization of Okara and Okara Nanocelullose Derived from Soybean Industrial Waste for Biosorbent Applications - Puspitasari, Dita; Asri, Lia Amelia Tresna Wulan; Syarif, Nur Fadhilah (Mesin, 2023)
Solid waste from tofu production, also known as okara, has numerous applications and can produce high-value-added products. However, the utilization of okara in Indonesia is not yet significant. This written work proposes okara as a source of nanocellulose to produce wastewater adsorbents in freshwater by fabricating it as aerogels and hydrogels. Wastewater is highly hazardous to the environment and living organisms as it can contain saturated salts, heavy metals, organic compounds, oil emulsions, dyes, and even microbes as pollutants that can lead to various diseases or death. Therefore, research on biosorbents is always a hot topic. Biosorption is the process of binding metal ions into the cellular structure of biological materials. Lignocellulosic biosorbents have high adsorption properties due to their ion exchange capability. Okara biosorbent can increase the absorption capacity of Pb2+ ions by up to 20% compared to conventional absorbents. The soybean skin component could also remove contaminated textile dyes from water. Additionally, the low lignin content in okara makes it easier to utilize than other lignocellulosic materials. This research study also shows that okara-based nanocellulose aerogels can maintain their shape or exhibit full shape recovery properties even after being used repeatedly.